(untitled) (Wudil Journal of Science and Technology Education, 2025)
The experiment was conducted at the Center for Agricultural Research, School of Agriculture and Agricultural technology of the Federal University of Technology Owerri, Imo State, Nigeria between January, 2023 – January, 2024 to estimate the heritability, variance components and genetic advance as the percentage of the mean of garri quality traits in cassava varieties cultivated in Okuku (Okuku locals) along some improved varieties. Three local varieties were sourced from a subsistence farmer in Okuku, Owerri-West, Imo State and five improved varieties were sourced from National Root Crop Research Institute (NRCRI), Umudike, Abia State. Each cassava variety was planted in a 12x1m (12m2).plot size at a planting distance of 1mx1m. The experiment was laid out in a Randomized Complete Block Design (RCBD) with four replications. Cassava stem cuttings of about 20cm with at least four nodes were planted on ridges, at 48 weeks after planting; the eight cassava varieties were harvested and processed into garri. The garri quality traits were grouped into: functional properties, proximate composition and minerals composition. Data were collected on swelling index(%), bulk density(g/ml), water absorption capacity(%), moisture content(%), ash(%), dietary fiber(%), crude fat(%), crude protein(%), carbohydrate(%), calcium(%), sodium(%), phosphorus(%) and potassium(%). Data collected were subjected to analysis of variance (ANOVA) and means separation was done using Least Significant Difference (LSD). The Analysis of Variance showed significant differences (p < 0.05) among the cassava varieties evaluated. Nwajeni and TMS 164773 exhibited higher protein, swelling index, and mineral contents, and so, may be preferred for nutritional and functional quality. Conversely, IBA980505 with lower moisture content and higher carbohydrate may be favored for shelf stability and energy yield. Genetic parameters such as mean, range, coefficient of variation, variances, heritability in broad-sense and genetic advance as the percentage of the mean were estimated for the 13 different traits. The study demonstrated that the observed variation was predominantly genetic in nature for most traits. Heritability values range from 35.90 – 100. 43Traits with the highest Genetic Advance as Percentage of Mean (GAM) were Ash (145.45%), Calcium (Ca) (122.22%), Crude Fiber (CFr) (45.45%), and Crude Fat (CF) (44.28%)., the combination of high heritability and high genetic advance for traits like Ash, Ca, CF, and CFr suggests that direct phenotypic selection remains the most efficient and rapid approach to improving key garri quality attributes